Kekuatan Pembuktian Saksi Testimonium De Auditu Dalam Tindak Pidana Kejahatan Terhadap Kesusilaan (Tinjauan Putusan Perkara Pengadilan Negeri Surabaya Nomor 1361/Pid.B/2022/PN. Sby) - Kristanto, Respati Bayu; Puspitosari, Hervina (Universitas Ekasakti, 2023)
This research aims to determine the evidentiary strength of testimonium de auditu and its position as a witness in trials of crimes against morality. This research uses normative legal research methods with a statutory approach, a case approach using Surabaya District Court Decision Number 1361/Pid.B/2022/PN Sby. The data collection instrument was carried out through secondary data obtained from literature. The data obtained is in the form of primary legal materials, secondary legal materials and tertiary legal materials. The data is then arranged systematically through an emphasis on understanding using qualitative descriptive methods. The results of this research indicate that the position and strength of a testimonium de auditu witness in a court trial is valid in accordance with the Constitutional Court decision No. 65/PUU-VIII/2010 and its strength depends on the conformity between the facts in the field and the witness' testimony in the trial. Then, further regulation is needed in the future regarding the meaning of witness testimonium de auditu in the upcoming revision of the Criminal Procedure Code regarding the differences in meaning with Constitutional Court Decision No. 65/PUU-VIII/2010 for the sake of implementing justice as well as legal certainty in a criminal justice process.